2012
DOI: 10.1007/s11524-012-9679-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Parental Perception of Neighborhood Safety and Asthma Diagnosis in Ethnic Minority Urban Children

Abstract: Low-income populations, minorities, and children living in inner cities have high rates of asthma. Recent studies have emphasized the role of psychosocial stress in development of asthma. Residence in unsafe neighborhoods is one potential source of increased stress. The study objective was to examine the association between parental perception of neighborhood safety and asthma diagnosis among inner city, minority children. Cross-sectional data from a community-based study of 6-8-year-old New York City children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Vangeepuram et al found that when parents were asked about various aspects of neighborhood safety, both safety while walking in the neighborhood and safety from crime were associated with a diagnosis of asthma among their children. However, other aspects of neighborhood safety such as conditions of sidewalks and adequacy of street lighting were not . Thus exposure to violence may play an important role in explaining the association between perceived neighborhood safety and asthma morbidity in our study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Vangeepuram et al found that when parents were asked about various aspects of neighborhood safety, both safety while walking in the neighborhood and safety from crime were associated with a diagnosis of asthma among their children. However, other aspects of neighborhood safety such as conditions of sidewalks and adequacy of street lighting were not . Thus exposure to violence may play an important role in explaining the association between perceived neighborhood safety and asthma morbidity in our study.…”
Section: Discussionmentioning
confidence: 69%
“…Asthma is one of the most common chronic diseases affecting children in the United States, 1 particularly among those living in poor, urban environments. 2 It is therefore essential to understand factors that lead to disparities and worsened outcomes in this population. Among the many elements that affect asthma morbidity, exposure to psychosocial stress appears to be very important.…”
Section: Introductionmentioning
confidence: 99%
“…These data only account for reported crime, so prevalence of asthma may be underestimated. This study demonstrated the utility of directly measuring crime, while Coutinho, McQuaid, and Koinis-Mitchell (2013) and Vangeepuram, Galvez, Teitelbaum, Brenner, and Wolff (2012) measured perceived safety.…”
Section: Resultsmentioning
confidence: 83%
“…Measuring safety was done both directly by looking at crime data (Gupta et al, 2010) and indirectly by measuring the perception of safety (Coutinho, McQuaid, & Koinis-Mitchell, 2013; Koinis-Mitchell et al, 2012; Vangeepuram, Galvez, Teitelbaum, Brenner, & Wolff, 2012). Gupta et al (2010) utilized surveys of children from kindergarten through eighth grade ( N = 45,371).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation